Study of silica gel as self-healing agent in geopolymer mortar exposed to extremely high temperature - Low, Wei Keat (2015)
Geopolymer can be used to produce structural concrete without the consideration on the emission of carbon dioxide as what Portland cement did. Geopolymer are produced when alumino-silicate, like fly ash mixed with a strong alkaline solution. The production of geopolymer is more economical and sustainable than normal cement. Durability of a structure is one of the concern for the engineers. In order to maintain the strength characteristic of the geopolymer, way to prolong the lifespan and cater the durability problems caused by cracks after high temperature exposure. Presence of self-healing agent contributes to the enhancement on the strength characteristic of the geopolymer concrete after high temperature exposure. There are several type of self-healing agent which can be used in geopolymer, such as: Poly Methyl Acrylate, silica gel, tung oil,silicone and bacterial solution. Silica gel will be used for this research as a self-healing agent. The main objective of this research is to determine the strength performance of self-healing geopolymer mortar after high temperature exposure. This research is conducted along with the following sub-objectives which is to identify the suitability of silica gel as self-healing agent in geopolymer mortar after exposed to extremely high temperature and the effectiveness of silica gel as self-healing agent in geopolymer mortar. Samples were subjected to elevated temperature of 500, 600 and 700 °C. The highest compressive strength achieved with the inclusion of silica gel in the specimen was 63.579 MPa which is higher than normal concrete. The compressive strength of the geopolymer mortar is also preserved after high temperature exposure. The performance of the geopolymer concrete is enhanced with the presence of the self-healing agent as the micro cracks are filled. The compressive strength of geopolymer was preserved even after exposure to 500 °C in the furnace for 30 minutes. Samples showed that the compressive strength decreased exponentially from 600 °C onwards which indicated geopolymer started to fail structurally. At 500 °C, the compressive strength did not have significant difference where there are only slight reduction in the specimens. As a conclusion, the objectives of this research have been fulfilled. Silica gel is suitable for the self-healing mechanism to take place. However, the silica gel should be replaced with non-commercial silica gel to ensure that the effect of self-healing mechanism take place with better framework produced through the reaction of the silica gel with the geopolymer